Chemical composition of essential oil Erythroxylum coca Lam var. coca (Coca) and evaluation of its antibacterial activity - Ventura, G. (2009)
The study was to evaluate the essential oil of Erythroxylum coca Lam. var. coca (Coca) - from Quillabamba province, Cusco region and determine its antibacterial activity, and elucidate the same chemical composition by Gas Chromatography / Mass Spectrometry (GC / MS). The plant part used the dried leaves were provided by the National Coca Company ENACO SA, which dealt with a system by steam distillation of water. The essential oil yield was 0.08% v/p and on that physicochemical tests were performed: Miscibility, density and refractive index. In the chemical composition found the following components: Guai-1(5),(11)-diene, t-cadinene, (2E,7R,11R)-3,7,11,15-tetramethyl-2-hexadecan-1 -ol, eudesm-4(14)-en-11-ol, hexahydrofarnesil ketone, hexadecanoic acid, phytol, cis-9-octadecenoic and octadecanoic acid. The study of antibacterial activity in vitro, using the method of excavation culture plate at concentrations of 10 and 50% of the oil showed greater activity to Staphylococcus aureus strain ATCC 25923, than against strains of Escherichia coli, Bacillus subtilis, Staphylococcus epidermidis and Pseudomonas aeruginosa ATCC 27853 strain. It was determined that the chemical components of essential oil of Erythroxylum coca Lam. Var coca (Coca) have antibacterial activity against Staphylococcus aureus.